O04.5 Point-of-care magnetofluidic assay cartridge for neisseria gonorrhoeae detection and antimicrobial resistance determination. (14th July 2019) - Trick, Alexander; Melendez, Johan; Chen, Liben; Hu, Tiffany; Gaydos, Charlotte; Wang, Tza-Huei
Abstract : Background: The rise of antimicrobial resistant (AMR) Neisseria gonorrhoeae (NG) has prompted worldwide concern over the looming possibility of untreatable gonococcal infections. A reduction of antimicrobial use by transitioning from generalized prescriptions to targeted pathogen-specific treatments would aid in treatment efficacy and reduce the risk of AMR NG development. However, actual implementation of such targeted treatments has been limited by the lack of rapid diagnostic tools that can provide antimicrobial susceptibility results at the point-of-care (POC). Methods: To address the need for a rapid NG screening test, we have developed a portable magnetofluidic instrument and corresponding assay cartridge. The assay cartridges use functionalized magnetic beads to couple nucleic acid extraction directly to a PCR-based duplexed nucleic acid amplification test (NAAT). The NAAT targets the opa gene for NG identification and the gyrA gene for characterization of ciprofloxacin susceptibility. In order to assess assay performance, we analyzed 27 well characterized NG strains and 29 swabs (20 urethral, 9 penile meatal) previously tested by culture. Results: The instrument has a compact footprint (5'x5.3'x3.3') and runs on a 5V, 2A power supply that can be provided by a small portable battery pack. Detection of NG and genotypic characterization of ciprofloxacin susceptibility was completed in <40 minutes. The cartridge-based assay correctly identified 100% (27/27) of the NG isolates as well as 100% (10/10) of the ciprofloxacin-resistant NG strains. All urethral and penile swabs were correctly identified as well (15/15 positive, 14/14 negative). Conclusion: Magnetofluidic assay cartridges allow automation of NAAT-based testing for NG and assessment of antimicrobial susceptibility. The portability, low power consumption, and ease-of-use of our platform has potential for enabling rapid diagnostics at the POC and in low-resource settings to guide targeted use of antimicrobials. Further studies with clinical samples are warranted. Disclosure: No significant relationships.